2014
DOI: 10.1097/01.aids.0000434936.57880.cd
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tuberculosis treatment on virologic and CD4+ cell count response to combination antiretroviral therapy

Abstract: Objectives To determine the impact of tuberculosis (TB) treatment at the time of combination antiretroviral therapy (cART) initiation on virologic and CD4 count response to cART. Methods Systematic review and meta-analysis of studies reporting HIV RNA and CD4 count response, stratified by TB treatment status at cART initiation. Stratified random-effects and meta-regression analyses were used when possible. Results 25 eligible cohort studies reported data on 49,578 (range 42-15,646) adults, of whom 8,826 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
5
10
1
Order By: Relevance
“…This is similar to the situation in adults 8 and reinforces WHO recommendations to initiate cART soon after TB treatment is tolerated. 4 In young children, our exploratory sensitivity analyses suggest that the combination of TB treatment and super-boosted LPV/r-based cART may increase the risk of rebound and diminish CD4% reconstitution.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is similar to the situation in adults 8 and reinforces WHO recommendations to initiate cART soon after TB treatment is tolerated. 4 In young children, our exploratory sensitivity analyses suggest that the combination of TB treatment and super-boosted LPV/r-based cART may increase the risk of rebound and diminish CD4% reconstitution.…”
Section: Discussionsupporting
confidence: 80%
“…In adults, receiving TB treatment at time of cART initiation does not impair virologic or immunologic response to cART, 8 though it may be associated with an increased risk of long-term mortality. 9 Results of limited pediatric research to date suggest that starting cART during TB treatment improves survival, 10-12 and that concomitant TB treatment and cART does not increase mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that individuals receiving TB treatment at the time of ART initiation have similar CD4 þ cell count increases during ART [15]. Our findings provide further support for this and indicate that ART can effectively restore CD4 þ cell counts in individuals presenting with HIV-TB co-infection, despite the numerous challenges faced in the management of these cases [4].…”
Section: Discussionsupporting
confidence: 76%
“…Potential mechanisms for impaired CD4 þ responses in the presence of HIV-TB co-infection include the practical difficulties associated with concurrent therapy, as well as possible immunological mechanisms due to increased T-cell activation and apoptosis [14]. A recent systematic review suggested that CD4 þ cell reconstitution appeared similar in individuals receiving TB treatment at the time of ART initiation compared to those who did not have co-existent TB [15]. However, due to study heterogeneity, a meta-analysis was not possible; considerable debate therefore remains regarding the impact of TB on CD4 þ responses to ART.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced viral suppression in young children on tuberculosis co-treatment when on a ritonavir-boosted lopinavir-based regimen has been previously reported. 23-26 Although efavirenz is also metabolized by the same hepatic enzyme system, there does not appear to be a requirement to increase its dose, nor is there the need for any additional drug to boost its levels, thereby making this regimen option the more suitable alternative.…”
Section: Discussionmentioning
confidence: 99%